2022
DOI: 10.4269/ajtmh.21-1339
|View full text |Cite
|
Sign up to set email alerts
|

Making Statistical Sense of the Molnupiravir MOVe-OUT Clinical Trial

Abstract: Oral therapies for the early treatment of COVID-19 may prevent disease progression and health system overcrowding. A new oral therapeutic named molnupiravir has been promoted as providing an approximately 50% reduction in death or the need for hospitalization. The clinical trial evaluating this drug was stopped early at the recommendation of the Data Safety and Monitoring Board after approximately 50% of the sample had been recruited. At the point of discontinuing the trial, approximately 90% of the planned sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…28,30 In fact, the MOVe-OUT trial has been criticized for its premature termination, imbalances of patient characteristics between treatment and control groups at baseline, inconsistency in the results between interim and final analyses that could not be fully explained by differences in patient characteristics, and the dubious value of molnupiravir given its modest reduction in hospitalization or death rate that failed to reach statistical significance (HR=0•69, 95%CI=0•48-1•01). 3,[30][31][32][33] Accordingly, further studies are needed to confirm the realworld effectiveness of molnupiravir and nirmatrelvir/ritonavir in different healthcare settings and COVID-19 patient populations. Several clinical trials (namely RECOVERY and PANORAMIC) and observational studies of the two oral antivirals are ongoing, which will take into account the circulating Omicron variant and vaccination status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…28,30 In fact, the MOVe-OUT trial has been criticized for its premature termination, imbalances of patient characteristics between treatment and control groups at baseline, inconsistency in the results between interim and final analyses that could not be fully explained by differences in patient characteristics, and the dubious value of molnupiravir given its modest reduction in hospitalization or death rate that failed to reach statistical significance (HR=0•69, 95%CI=0•48-1•01). 3,[30][31][32][33] Accordingly, further studies are needed to confirm the realworld effectiveness of molnupiravir and nirmatrelvir/ritonavir in different healthcare settings and COVID-19 patient populations. Several clinical trials (namely RECOVERY and PANORAMIC) and observational studies of the two oral antivirals are ongoing, which will take into account the circulating Omicron variant and vaccination status of patients.…”
Section: Discussionmentioning
confidence: 99%
“…10 The reason for this difference has been debated. 13 Several Phase 3 trials have been conducted in India among non-hospitalized patients with reportedly mixed findings, 14 but to date the full peer-reviewed results have not been published. The AGILE CST-2 trial conducted in 180 vaccinated and unvaccinated participants showed that molnupiravir resulted in a faster time to a negative PCR test compared with placebo (8 days versus 11 days).…”
Section: Introductionmentioning
confidence: 99%
“…Estimates were similar for all subgroups. The observed median (IQR) time-to-first-recovery from randomisation was 9 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) days in molnupiravir and 15 ( Interpretation In this preliminary analysis, we found that molnupiravir did not reduce already low hospitalisations/deaths among higher risk, vaccinated adults with COVID-19 in the community, but resulted in faster time to recovery, and reduced viral detection and load.…”
mentioning
confidence: 99%
“…Molnupiravir reduced the risk of hospital admission or death by 52% versus placebo in the interim analysis but raised risk by 35% among patients subsequently evaluated 4. There was no clear explanation for this substantial disparity in treatment effects between the interim and final phases.…”
mentioning
confidence: 89%